The construction of a questionnaire to measure social entrepreneurship in physical education - Carlos Capella Peris; Jesús Gil Gómez; Manuel Martí Puig; Paola Ruiz-Bernardo (Sociedad Iberoamericana de Pedagogía Social, 2016)
This article aims to design and validate an instrument that measures the social entrepreneurship of a group of university students participating in service-learning programmes in the field of Physical Education. Firstly, a literature review was carried out to determine the characteristics that define the social entrepreneur, to latterly develop an initial questionnaire that assessed these traits. After that, a logical review was undertaken, submitting the aforesaid questionnaire to various experts. Following a thorough screening process, the pilot questionnaire on which the empirical review was carried was defined and the questionnaire was applied amongst a sample of 188 subjects. The results of the logical review highlighted the quality, relevance and understanding of the selected items, with only 2 of the 19 characteristics of social entrepreneurship proposed being eventually discarded. The results of the empirical review gave a positive record, highlighting a total average of 3.82 points out of a possible 5. The validity and reliability of the questionnaire was evident as it obtained a score of 0.809 on Cronbach's alpha, which suggest the inner strength of the questionnaire. In regard to factor analysis, the items were grouped into three broad categories, an issue which despite not coinciding fully with the initial approach, did not vary greatly. Thus, we conclude that the elaborated tool fulfilled its initial objective, and was still valid to measure social entrepreneurship. Its usefulness is based on the importance of promoting this competency within any field, especially in the educational domain.